Early CT features and temporal lung changes in COVID-19 pneumonia in Wuhan, China. Issue 128 (July 2020) - Hu, Qiongjie; Guan, Hanxiong; Sun, Ziyan; Huang, Lu; Chen, Chong; Ai, Tao; Pan, Yueying; Xia, Liming
Abstract: Purpose: To analyse the high-resolution computed tomography (HRCT) early imaging features and the changing trend of coronavirus disease 2019 (COVID-19) pneumonia. Materials and Methods: Forty-six patients with COVID-19 pneumonia who had an isolated lesion on the first positive CT were enrolled in this study. The following parameters were recorded for each lesion: sites, sizes, location (peripheral or central), attenuation (ground-glass opacity or consolidation), and other abnormalities (supply pulmonary artery dilation, air bronchogram, interstitial thickening, etc.). The follow-up CT images were compared with the previous CT scans, and the development of the lesions was evaluated. Results: The lesions tended to be peripheral and subpleural. All the lesions exhibited ground-glass opacity with or without consolidation. A higher proportion of supply pulmonary artery dilation (89.13 % [41/46]) and air bronchogram (69.57 % [32/46]) were found. Other ﬁndings included thickening of the intralobular interstitium and a halo sign of ground glass around a solid nodule. Cavitation, calciﬁcation or lymphadelopathy were not observed. The reticular patterns were noted from the 14 days after symptoms onset in 7 of 20 patients (45 %). At 22–31 days, the lesions were completely absorbed only in 2 of 7 patients (28.57 %). Conclusion: The typical early CT features of COVID-19 pneumonia are ground-glass opacity, and located peripheral or subpleural location, and with supply pulmonary artery dilation. Reticulation was evident after the 2nd week and persisted in half of patients evaluated in 4 weeks after the onset. Long-term follow-up is required to determine whether the reticulation represents irreversible ﬁbrosis.